Green Innovation: Harnessing Photovoltaic Power in a Novel Mechanical Mixer for Wastewater Treatment (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The potential of photovoltaic solar energy in Iraq is plentiful but remains largely untapped, leaving many rural communities without grid access. There is an opportunity for stand-alone photovoltaic systems tailored to the electrical load, solar radiation, and location of underserved residential areas. The high upfront yet low operating costs of solar stand-alone systems can competitively electrify households. This article analyzes the design and economic feasibility of installing stand-alone solar photovoltaic systems to power residential areas currently off the grid in Iraq. Location-specific solar radiation data informs optimal system sizing. The electrical load demands of a typical Iraqi household determine the required system specifications. Detailed system sizing calculations and economic projections reveal the large upfront but ultimately worthwhile investments for solar electrification in rural Iraq. The article additionally examines mechanical mixing design, exploring the fluid dynamic forces exerted on impellers and consequent stresses on shafts and gear reducers. Transient flow asymmetries induce dynamic loading. The impeller-vessel interaction proves critical. Oil removal via coagulation-flocculation treatment shows promise, achieving heightened oil removal with a particular 4-bladed impeller system. Experiments systematically vary impeller speed and pH to optimize treatment conditions. The kinetics reveal key insights into maximizing treatment efficacy. Altogether, tailoring photovoltaic technology to rural areas and optimizing mixing reactor design usher renewable, off-grid electricity and improved wastewater treatment.